2023
DOI: 10.1088/1361-6560/acefa1
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation for proton dosimetry in magnetic fields: Fano test and magnetic field correction factors k B for Farmer-type ionization chambers

M Marot,
F Jäger,
S Greilich
et al.

Abstract: Objective: In this contribution we present a special Fano test for charged particles in presence of magnetic fields in the MC code TOPAS, as well as the determination of magnetic field correction factors kB for Farmer-type ionization chambers using proton beams.

Approach: Customized C++ extensions for TOPAS were implemented to model the special Fano tests in presence of magnetic fields for electrons and protons. The Geant4-specific transport parameters, DRoverR and finalRange, were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Henceforth, the settings in Kretschmer et al (2020) were considered adequate and can be applied in further chamber simulations in proton dosimetry in magnetic fields. Marot et al (2023) reported Fano test results within 0.82% ± 0.42% for 150 MeV proton beam in 1.5 T magnetic field using the TOPAS/Geant4 package within a slab geometry. Although they implemented a stricter step size limitation (dRoverRange and finalRange), their production cut corresponds to energy of 1 keV in the materials.…”
Section: Fano Cavity Testmentioning
confidence: 96%
“…Henceforth, the settings in Kretschmer et al (2020) were considered adequate and can be applied in further chamber simulations in proton dosimetry in magnetic fields. Marot et al (2023) reported Fano test results within 0.82% ± 0.42% for 150 MeV proton beam in 1.5 T magnetic field using the TOPAS/Geant4 package within a slab geometry. Although they implemented a stricter step size limitation (dRoverRange and finalRange), their production cut corresponds to energy of 1 keV in the materials.…”
Section: Fano Cavity Testmentioning
confidence: 96%